The differential burden of acute rhinovirus infections in children with underlying conditions - María Isabel Sánchez Códez; Isabel Benavente Fernández; Katherine Moyer; Amy L. Leber; Octavio Ramilo; Asuncion Mejias (PLoS ONE, 2025)
Introduction Rhinoviruses (RVs) are a well-known trigger of wheezing episodes in children with asthma. Their role in other pediatric chronic medical conditions is not fully known. Methods Patients ≤21 years hospitalized or evaluated as outpatients with symptomatic RV infection were identified from 2011–2013. Patients were categorized based on the type of underlying disease and differences in clinical parameters, RV loads (C T values), viral, bacterial and fungal co-infections and clinical outcomes were compared between groups. Multivariable analyses were performed to identify the comorbidities associated with oxygen requirement, PICU admission, and prolonged hospitalization. Results Of 1,899 children identified, 77.7% (n = 1477) had an underlying comorbidity including asthma/atopy (36.8%), prematurity (7.7%), chronic respiratory diseases (6.4%), congenital heart disease (CHD, 3.2%), immunocompromised hosts (ICH; 1.4%) and others (22.2%). Prevalence of comorbidities increased with age (70%, infants vs 84%-87%, children >1 year; p < 0.0001). Median RV loads were intermediate-high (24–26 C T values), irrespective of the underlying disease. RV/viral co-detections were identified in 11% of ICH vs 20%- 30% in all other children whereas bacterial co-infections were identified in 2.9% of children. Multivariable models identified asthma/atopy, prematurity, CHD and bacterial co-infections consistently associated with all three clinical outcomes (p < 0.0001). Older age and higher RV loads were also associated with increased odds of PICU admission. Conclusions The prevalence of comorbidities was high in children with RV infections. Of those, asthma/atopy, prematurity and CHD were consistently associated with severe disease. Higher RV loads and bacterial co-infections, although infrequent, were also associated with worse clinical outcomes, suggesting the importance of defining clinical phenotypes for future targeted interventions.